2018
DOI: 10.1186/s40069-018-0255-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural Behavior of Durable Composite Sandwich Panels with High Performance Expanded Polystyrene Concrete

Abstract: Sandwich panels comprising prefabricated ultra-high performance concrete (UHPC) composites can be used as ecofriendly and multi-functional structural elements. To improve the structural and thermal performance of composite sandwich panels, combinations of UHPC and expanded polystyrene (EPS) beads were investigated. High-performance expanded polystyrene concrete (HPEPC) was tested with various EPS bulk ratios to determine the suitability of the mechanical properties for use as a high-strength lightweight aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…The choice of core material depends on the type of application and the distinct target parameters. Every core has its own unique chemical, physical and mechanical features that can be considered for a specific design purpose . Along with weight and cost, strength, stiffness and energy absorption are usually the most demanding properties in the design of a sandwich structure .…”
Section: Sandwich Structuresmentioning
confidence: 99%
“…The choice of core material depends on the type of application and the distinct target parameters. Every core has its own unique chemical, physical and mechanical features that can be considered for a specific design purpose . Along with weight and cost, strength, stiffness and energy absorption are usually the most demanding properties in the design of a sandwich structure .…”
Section: Sandwich Structuresmentioning
confidence: 99%
“…The common typical cross section of structural precast sandwich panel (SPSP) consists of two face wythes of concrete separated by core wythe that almost consists of heat insulation material [1]. Various parameters control the structural behaviour and the overall ultimate capacity of structural precast sandwich panels such as the grade of concrete in concrete face wythes, thickness of concrete face wythes, distribution of shear connectors, rigidity of core material, and bond between core-concrete interfaces [1,2]. It was found that shear flow capacity tends to decrease with the increase of core wythe [1].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, ultra-high performance concrete was successfully the production of face wythes of SPSP with the core material of high performance expanded polystyrene. The panels were classified as light weighted high-strength structural sandwich panel [2]. The relative light weight comparing to high strength is playing the main role which controls the performance of SPSP [2,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, almost all commercial EPS beads are produced by suspension polymerization . Therefore, halogen‐free flame‐retardant EPS beads prepared by suspension polymerization can be popularized on a large scale without changing the existing production process . Many researchers have investigated this topic.…”
Section: Introductionmentioning
confidence: 99%